2023
DOI: 10.1093/jbcr/irad041
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Ellagic Acid on Immune Function in Burned Rats

Abstract: To investigate the effect of ellagic acid (EA) treatment on immune function in burned rats. First, 30 Sprague-Dawley rats were established as a deep second-degree burn model. They were randomly divided into three groups: Model group, EA 50 mg/kg, and EA 100 mg/kg group. The wound area of rats at 0–7 days was measured and the wound healing rate was calculated. The levels of inflammatory factors tumor necrosis factor-α (TNF-α), interferon γ (IFN-γ), interleukin (IL)-1β, IL-6, IL-10, and immunoglobulins IgA, IgG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In an in vivo study of rats conducted by Deng et al, the treatment of skin burns with ellagic acid (at 50 or 100 mg/kg) was found to significantly reduce serum concentrations of IgA, IgG, IgM, TNF-α, IFN-γ, IL-1β, IL-6, and IL-10, while significantly increasing CD4+/CD8+ T cell and CD4+ CD25+ Treg cell counts, and decreasing the Foxp3 + T cell count. These changes suggest an anti-inflammatory effect and improvements in the immune system [ 53 ]. BenSaad et al [ 51 ] attributed the anti-inflammatory effects of ellagic acid, gallic acid, and punicalagin on liposaccharide-treated RAW267.4 cells to the capacity of these polyphenols to inhibit nitric oxide, prostaglandin E2, and IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study of rats conducted by Deng et al, the treatment of skin burns with ellagic acid (at 50 or 100 mg/kg) was found to significantly reduce serum concentrations of IgA, IgG, IgM, TNF-α, IFN-γ, IL-1β, IL-6, and IL-10, while significantly increasing CD4+/CD8+ T cell and CD4+ CD25+ Treg cell counts, and decreasing the Foxp3 + T cell count. These changes suggest an anti-inflammatory effect and improvements in the immune system [ 53 ]. BenSaad et al [ 51 ] attributed the anti-inflammatory effects of ellagic acid, gallic acid, and punicalagin on liposaccharide-treated RAW267.4 cells to the capacity of these polyphenols to inhibit nitric oxide, prostaglandin E2, and IL-6 production.…”
Section: Discussionmentioning
confidence: 99%